2019
DOI: 10.1002/nau.24037
|View full text |Cite
|
Sign up to set email alerts
|

Acute spinal cord injury is associated with mitochondrial dysfunction in mouse urothelium

Abstract: Aim To characterize the effects of acute spinal cord injury (SCI) on mitochondrial morphology and function in bladder urothelium and to test the therapeutic efficacy of early treatment with the mitochondrially targeted antioxidant, MitoTempo. Methods We used a mouse model of acute SCI by spinal cord transection between the T8‐T9 vertebrae with or without MitoTempo delivery at the time of injury followed by tissue processing at 3 days after SCI. Control, SCI, and SCI‐MitoTempo‐treated mice were compared in all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…A previous animal study indicated that SCI induced inflammatory changes with effects on the innate immune system within the host before, during, and after UTI episodes [ 12 ]. Another animal study of acute SCI showed that SCI had negative and severe effects on mitochondrial health in the bladder urothelium [ 29 ]. Similar results were demonstrated in the present study, as patients with SCI presented with higher level of TP63, Ki-67, BAX, tryptase, TNF-α, and TGF-β, regardless of the occurrence of a recent rUTI.…”
Section: Discussionmentioning
confidence: 99%
“…A previous animal study indicated that SCI induced inflammatory changes with effects on the innate immune system within the host before, during, and after UTI episodes [ 12 ]. Another animal study of acute SCI showed that SCI had negative and severe effects on mitochondrial health in the bladder urothelium [ 29 ]. Similar results were demonstrated in the present study, as patients with SCI presented with higher level of TP63, Ki-67, BAX, tryptase, TNF-α, and TGF-β, regardless of the occurrence of a recent rUTI.…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondria-targeted antioxidants MitoQ and MitoTEMPO have been successfully used to improve some disease phenotypes of cardiovascular disease [ 21 , 27 , 30 , 31 , 32 ], inflammation [ 22 , 23 ], neurodegenerative disorders [ 33 , 34 , 35 , 36 , 37 ], and diabetes [ 38 , 39 ]. Thus, testing these compounds in other ROS-related disorders such as cancer is highly relevant, particularly as mitochondria-associated ROS are known to stimulate cell proliferation and tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…The electron transport system, especially the respiratory complexes, are frequent tar-gets. Acquired mitochondrial defects are usually caused by toxins, medications, or aging, and are observed in numerous diseases and pathologies including chronic kidney diseases, 32 uremia, 33 cardiac infarctions, 34 cardiac surgery, 35 atherosclerosis, 36 organ transplantations, 37 strokes, 38 spinal cord injury, 39 traumatic brain injury, 40 obesity, 41 diabetes, 42 insulin resistance, 43 as well as age-related disorders such as Alzheimer's and Parkinson's diseases, and various types of cancers. 44 Generally, cells that are highly metabolically active and those that replicate rapidly require larger numbers of mitochondria and tend to be more susceptible to damage compared to metabolically inactive cells.…”
Section: The Clinical Problemmentioning
confidence: 99%